First-principles studies on the superconductivity of aluminene - Yeoh, Keat Hoe; Yoon, Tiem Leong; Rusi, -; Ong, Duu Sheng; Lim, Thong Leng (Elsevier, 2018)
Group III mono-elemental two-dimensional (2D) materials have been an active area of research since the experimental demonstration of monolayer boron. Using first-principles calculations, we predict a new type of buckled monolayer aluminum (aluminene) which exhibits metallic characteristics. From the phonon dispersion and cohesive energy calculations, the free-standing aluminene is structurally stable. The stability of the aluminene is maintained under tensile strain up to 7%. In contrast, the stability of the structure is not preserved in the presence of compressive strain. We also carried out a systematic analysis on the electron–phonon coupling in the aluminene structure and found that aluminene in its pristine form can superconduct with superconductivity critical temperature, Tc of 6.5 K. The Tc is further enhanced to 11.9 K with the presence of 7% bi-axial tensile strain. Our calculations show that the higher Tc is because of stronger electron–phonon coupling resulted from the increase of density of states at Fermi level with tensile strain.